Measurement Errors in Yield Stress Rheometry that Arise from Torque Auto Zero - Fisher Daniel T.; Boger David V.; Scales Peter J. (Applied Rheology, 2006)
The measurement of the shear rheology of concentrated particulate suspensions is important to a range of mixing, pumping and flow operations. The use of a four or six bladed vane attached to a rheometer in an open cup is a popular technique to achieve a rheological characterisation. A problem occurs in the use of automated software with a number of rheological devices for yield stress materials. A torque auto zero default causes the torque at the start of a test to be ignored, and can result in significant errors and underestimation of the yield stress or rheological response of the suspension. The potential effect of using a torque auto zero default is demonstrated for a concentrated particulate suspension of nickel laterite.